Membangun Generasi Peduli Lingkungan: Implementasi Pendidikan Konservasi pada Anak Usia Dini di PAUD Al-Fatah Temboro - Alip Laila Bintar Wati; Khoirun Nisa (Institut Agama Islam Negeri Madura, 2025)
Conservation education is essential for early childhood as it instills environmental care values from an early age, builds nature-responsible character, and creates environmentally conscious generations. This research aims to foster environmental care attitudes among early childhood education students. The study employed a qualitative descriptive method involving ten students and one classroom teacher. Data collection techniques included observation, interviews, and documentation. The results revealed that teachers' conservation education efforts at PAUD Al-Fatah Temboro were implemented through various methods: direct practical activities, Islamic storytelling, habituation, and role modeling. Besides involving school community members, teachers also collaborated with parents to achieve optimal learning objectives. Routine programs such as classroom cleaning duties, Clean Friday activities, and plant care proved effective in nurturing environmental awareness among early childhood students.